The Right of Asylum in New Mexico in the Seventeenth and Eighteenth Centuries - Howard West, Elizabeth ((New Mexico Historical Review))
Este parece ser un sobretiro de la New Mexico Historical Review, sin embargo, no contamos con fecha o número de volumen.